ICONOGRAPHY OF FIFTEEN SCULPTURES FROM THE KHORDHA DISTRICT OF ODISHA - Mohapatra, Ratnakar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The article aims to highlight the iconographic character of the fifteen old sculptures from the Khordha district of Odisha. The characteristic features of the fifteen sculptures of Khordha district is the main facet of the sculptural art of Odisha. In the survey of two historical sites of Khordha district like Kenduli, and Bhavani Shankar temple complex of Bhubaneswar, sculptures of different sects are found to be worshipped by the people/devotees with great enthusiasm. Among these, fifteen sculptures have been documented in this article by the author. The present Khordha district is originated from the undivided Puri district of the state. The regions of undivided Puri district are found studded with various temples of different sects. Here, the author has documented fifteen sculptures/images from the two sites of the modern Khordha district. The sculptures of various deities of the two sites of the Khordha district are found designed with the traditional attributes and ornaments. Sculptural points of view, the surveyed fifteen sculptures of the Khordha district are very significance, for which, the author has thoroughly surveyed these images. The sites of these fifteen sculptures are viz; six from the Jayadev Museum, Kenduli, and nine from the Bhabani Shankar temple complex of the old town of Bhubaneswar. The names of these surveyed fifteen sculptures of the two sites of the Khordha district are such as 1. Vishnu, 2. Vishnu, 3. Bhairava, 4. Siva-Nritya, 5. Astika-Jaratkaru, 6. Vishnu, 7. Kartikeya 8. Siva, 9. Sivalinga with four heads of Lord Siva, 10. Siva-Parvati, 11. Kartikeya, 12. Ananta Narayana, 13. Hara-Parvati, 14. Lakshmi, and 15. Buddha. Iconographic features of these fifteen sculptures of Khordha district require a serious study. Hence, the author has made a noble effort to undertake this research work. The primary as well as secondary sources have been used in this piece of work